2007
DOI: 10.1111/j.1463-1326.2006.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved glycaemic control of thrice‐daily biphasic insulin aspart compared with twice‐daily biphasic human insulin; a randomized, open‐label trial in patients with type 1 or type 2 diabetes

Abstract: This trial confirmed that a thrice-daily BIAsp regimen can safely be used to intensify treatment for patients inadequately controlled on twice-daily BHI. A treat-to-target trial is required to explore the full potential of the BIAsp regimens and evaluate their use as a viable alternative to intensification with a basal-bolus regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 20 publications
(15 reference statements)
5
34
0
Order By: Relevance
“…30 Furthermore, BIAsp therapy has even been shown to achieve glycemic control equivalent to that of basal-bolus therapy using insulin aspart and NPH insulin. 31 In this study, the BIAsp group administered BIAsp 50 or 70 (depending on body mass index) at breakfast and lunch, plus BIAsp 30 at dinner, which resulted in a mean HbA 1c reduction of 1.3% in 16 weeks-the same as that for the basal-bolus group, indicating that different mixture ratios help to achieve major reductions in HbA 1c .…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, BIAsp therapy has even been shown to achieve glycemic control equivalent to that of basal-bolus therapy using insulin aspart and NPH insulin. 31 In this study, the BIAsp group administered BIAsp 50 or 70 (depending on body mass index) at breakfast and lunch, plus BIAsp 30 at dinner, which resulted in a mean HbA 1c reduction of 1.3% in 16 weeks-the same as that for the basal-bolus group, indicating that different mixture ratios help to achieve major reductions in HbA 1c .…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of using mid-/high-mix formulations is that they offer a greater insulin load around mealtimes and, therefore, better postprandial glucose control 2 . The use of BIAsp 30/50/70 has been investigated in several RCTs, which have shown that glycemic control can be improved by switching to BIAsp (three-times daily) from BHI therapy (twice daily), although there may be a higher risk of minor hypoglycemia [31][32][33][34] . The results of these studies also indicate that it may be better to use BIAsp 30 for the evening dose to decrease the risk of nocturnal hypoglycemia 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Chadha showed data from two recent studies demonstrating clear benefits of high ratio premixed insulins on postprandial glucose profile and overall metabolic control in people with type 2 diabetes. 51,52 Keynote Lecture: The Selfish Brain-Conflicting Interests Between Brain and Body Can Help to Explain Why Diets Often Fail Achim Peters, Luebeck, Germany…”
Section: Monitoring and Treatment Of Pphmentioning
confidence: 99%